Why people want to be volunteer in a hospice? The motivations of people taking on the role of medical volunteer in a hospice. - Szeliga, Marta; Mirecka, Jadwiga (Nursing Problems / Problemy Pielęgniarstwa, 2016)
Introduction. Volunteers are important members of the team who takes care of patients in a hospice. The role of hospice’s volunteers is demanding and hard. Authors of the study decided to check why people voluntarily and free of charge undertake to perform such a difficult function. Aim uf the study. Recognition the motivation of people declaring their intention to become a medical volunteer in a hospice. Material and Methods. The study was carried out in St. Lazarus Hospice in Krakow and included 169 candidates participating in four consecutive editions of “A course for volunteers – a guardian of the sick” organized by the hospice. The analysis of their motivation was carried out on the basis of an anonymous questionnaire and interviews. Results. The most frequently indicated by the candidates reason for applying for hospice volunteering was “desire of doing something good for others” (96,3%). More than half of the examined also felt "the need to acquire new skills" (57.4%) or did so for religious reasons (50.6%). Least likely indicated motives were, "the need for organizing of free time" and the "need to demonstrate extra activity in CV" (both the 9.3%). Conclusions. The motivations of people who want to join the group of hospice volunteers are generally altruistic, and frequently stated motive is "desire of doing something good for others". A more relevant way to learn the real motivation of the volunteer is sincere conversation with him than a written survey.